Analisis Putusan Bawaslu Provinsi Gorontalo Dalam Penyelesaian Penanganan Pelanggaran Administrasi Pindah Memilih - Laode, Nadila Magfira; I. Rahim, Erman; Ahmad, Ahmad (PT. Meja Ilmiah Publikasi, 2025)
This study aims to analyze how the Gorontalo Provincial Election Supervisory Body (Bawaslu) issued a decision regarding the settlement of administrative violations regarding voters moving in the election. This study utilizes a normative approach in a qualitative way and analyzes Bawaslu's decisions and relevant laws and regulations. Data collection techniques were carried out through reviewing Bawaslu's decision files and question and answer sessions with interested parties at the election stage. The findings reveal that although Bawaslu's decisions generally incorporate adequate legal reasoning, there remain inconsistencies in the application of norms and procedural standards. Notably, some rulings lack clarity in defining the specific administrative violations, leading to potential legal uncertainty for voters and electoral participants. The study underscores the importance of establishing more consistent and transparent standards in administrative violation adjudication to enhance legal certainty, especially in cases involving voter relocation. The research provides both academic insights and practical recommendations for improving the quality of Bawaslu’s decisions in future elections.